Changes of Ankle Motion and Ground Reaction Force Using Elastic Neutral AFO in Neurological Patients with Inverted Foot During Gait - Du-Jin Park; Young-In Hwang (Actuators)
Many stroke patients develop ankle deformities due to neurological or non-neurological factors, resulting in abnormal gait patterns. While Ankle-Foot Orthoses (AFOs) are commonly used to address these issues, few are specifically designed for ankle varus. The Elastic Neutral Ankle-Foot Orthosis (EN-AFO) was developed for this purpose. This study aimed to analyze changes in kinematic and kinetic gait data in stroke patients with ankle varus, comparing those walking with and without EN-AFO in both AFO and No-AFO groups. Initially, 30 stroke patients with ankle varus were screened; after exclusions, 17 were included in the final analysis. In the No-AFO group, EN-AFO significantly improved maximal ankle inversion on the affected side during the swing phase (from 4.63 ± 13.26 to 10.56 ± 11.40, p = 0.025). Similarly, in the AFO group, EN-AFO led to a significant improvement in maximal ankle inversion on the less-affected side during the swing phase (from 7.95 ± 10.11 to 12.01 ± 8.64, p = 0.021). Additionally, ground reaction forces on the affected side of the AFO group significantly increased at both the forefoot (from 182.76 ± 61.45 to 211.55 ± 70.57, p = 0.038) and hindfoot (from 210.67 ± 107.88 to 231.85 ± 105.38, p = 0.038) with EN-AFO. Conversely, maximal and minimal thoracic axial rotation on the affected side improved significantly in the No-AFO group compared to the AFO group with EN-AFO, during both the stance and swing phases (stance phase: max improvement from −1.13 ± 1.80 to 4.83 ± 8.05, min improvement from −1.06 ± 2.45 to 5.89 ± 7.56; swing phase: max improvement from −1.33 ± 2.13 to 5.49 ± 7.82, min improvement from −1.24 ± 2.43 to 5.95 ± 7.12; max p = 0.034, min p = 0.016 during stance; max p = 0.027, min p = 0.012 during swing). Furthermore, both maximal and minimal thoracic axial rotation on the less-affected side during the swing phase improved significantly in the No-AFO group (max improvement from −2.09 ± 4.18 to 6.04 ± 6.90, min improvement from −0.47 ± 2.13 to 8.18 ± 10.45; max p = 0.027, min p = 0.012) compared with the AFO group. These findings suggest that EN-AFO may effectively improve gait in stroke patients with ankle varus in the No-AFO group.